Awareness of Smokeless Tobacco among Professionals with Sedentary Lifestyles- A Cross Sectional Study - Shitanshu Malhotra; Pallavi Singh; Himangi Dubey; Gaurav Mishra; Neha Agarwal (Wolters Kluwer Medknow Publications, 2021)
Background: Smokeless tobacco is tobacco orally consumed and not burned. Smokeless tobacco is associated with substantial risks of oral cancer. Smokeless tobacco is the cheapest and very commonly used tobacco product in India. It is highly addictive, is high in carcinogens, and causes a broad spectrum of diseases; yet awareness about its ill effects is low. Aim: The aim is to provide descriptive information on the awareness of smokeless tobacco among software professionals with sedentary lifestyles in Lucknow city, Uttar Pradesh. Subjects and Methods: A descriptive cross-sectional questionnaire survey was conducted. The sampling technique adopted for this study was the two-staged simple random sampling. The first stage consisted of division of city, and then selection of samples was done randomly in the second stage. After giving consent to participate in the study, the final study population was 500 professionals (320 males and 180 females). The 23-item self-administered structured questionnaire with closed-ended questions was formulated. Chi-square test was used to compare the categorical data. Analysis was performed on Statistical Package for the Social Sciences software SPSS, ver. 20.0; SPSS Inc., Chicago, IL, USA. Results: The prevalence of smokeless users among professional was 28.4%. The knowledge of awareness about ingredients (P = 0.016) and harmful effects (P = 0.038) of smokeless tobacco was significantly (P < 0.05) higher among users as compared to nonusers. In contrast, the knowledge about harmful types (betel quid, pan masala with tobacco, pan masala without tobacco, and all these) was higher in nonusers than users (P = 0.021). Conversely, users are significantly more familiar with counseling techniques for quitting tobacco than nonusers (P = 0.017). Conclusion: Most of the software professionals continued the habit of chewing in spite of good knowledge about the hazards of smokeless tobacco. The prevalence of smokeless tobacco users among professionals was 28.4%. Higher prevalence of pan masala with tobacco among professionals was demonstrated by this study, which is not a good sign for the future toward tobacco control.